BEST AIRFOIL NACA 0013 ATTACK ANGLE WHEN TAKING OFF - Hidayat, M Fajri; Nofendri, Yos (JURNAL KAJIAN TEKNIK MESIN, 2021)
The aerospace world in Indonesia is increasingly lethargic, it takes talented researchers in the field of Aerodynamics in order to reestablish the good name and dignity of the Nation. My research this time aims the field of aerodynamics of the cross section of airfoil aircraft wing type NACA 0013 by finding the right angle of attack for Take Off. The method I use with the application of CFD Simulation using Software ANSYS-Fluent version 14.5 with Workbench. The results obtained from this study will be tabulated in the table and graph of the relationship between the Lift to the Angles of Attack. By taking variable angle of attack as much as 9 variables that is 0o, 3o, 6o, 9o, 12o, 15o, 18o, 21o, and 24o. From the Simulation results obtained the best angle of attack for the type of NACA 0013 is 21o with the price of Lifting Force of 61,650 N.Keywords : Aerospace; Airfoil NACA 0013; Angle of Attack; ANSYS Fluent; Lift